Implementation of Local Agency Performance Accountability System Policy in Realizing Good Governance in Papua: An Influencing Factors - Blasius Sejati (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2019)
This study uses a qualitative approach, data collection techniques using interviews, observation, and documentation. Checking data credibility is done by using data triangulation technique, the collected data is then organized, interpreted, and analyzed repeatedly to draft the research findings. The results of the research show that the constraints of the inhibiting factors in the implementation of the Government Agency Performance Accountability System policy in Keerom Regency, the researchers argue that it should use the SEJATI implementation approach model, namely: this model stands for the High-Performance System, this model results from the development of the implementation model according to Van Meter and Van Horn. This model presupposes that policy implementation runs linearly from political decisions, implementing that policy performance is influenced by several phenomena, namely: (1) Standards and objectives of policies / measures and policy objectives; (2) Human and Financial Resources; (3) Characteristics of local implementing organizations; (4) Employee Work Culture; (5) Communication between related organizations and implementation activities; (6) Social, economic, social and political environment; (7) a harmonious and humanistic work culture.